Sobotify: A Framework for Turning Robots into Social Robots - Hubert, Heiko; Yun, Hae Seon (2024 19th ACM/IEEE International Conference on Human-Robot Interaction (HRI), 2024)
Sobotify is a software framework, which aims at simplifying the process of using robots in the field of social robotics. This paper delineates the design and usage of the framework. With Sobotify, even non-technical people should be enabled to use robots for their specific purposes, such as teachers in a classroom, therapists in a physiological or psychological therapy or childcare workers in kindergarten. During the development process of Sobotify, feedback from teachers at a vocational school have been taken into account in order to adjust the tools to their needs. The framework is designed to work with different robots including both humanoid (NAO and Pepper) and non-humanoid robots such as toy robots (Cozmo) with advanced abilities as well as very simple toy robots (MyKeepon). The framework was tested by two research works which proved that Sobotify is applicable in different setups. Further development is already planned for the next months, e.g. integration of additional robots and extension of tools.CCS CONCEPTS* Computer systems organization → Robotic control; * Applied computing → Interactive learning environments; * Humancentered computing → Systems and tools for interaction design.